Alternative supplementary biochemic food for growing up the fresh water lobster (Cherax quadricarinatus) - EDI PRIYONO; OKID PARAMA ASTIRIN; PRABANG SETYONO (Nusantara Bioscience, 2009)
Priyono E, Astirin OP, Setyono P. 2009. Alternative supplementary biochemic food for growing up the fresh water lobster (Cherax quadricarinatus). Nusantara Bioscience 1: 123-130. This research denotes to know the influence of biochemic composition to the rapid grow of fresh water lobster on the stadium of post larva (PL) of 60 within three months. This research used the complete random planning dealing with 4 treatments and each treatment would get 3 times cycle. The treatments cover, group K tested animal was treted with 100% mill food containing 30% of protein. Group A is given with food and biochemic food containing 13,34% of protein. Group B is the treated with mill food which is mixed with biochemic food containing 10,7% of protein. While group C was tested by treating them with mill food and biochemic food containing 13,58%. After all the above mentioned would be set up within 3:1 comparation. The variable of this research were the length of the abdomen, cephalothorax, total length, and the wet weight. The data analysis is using ANOVA system on 95% power test completed by of SPSS version 13. The result of the research shows that mentioned treatments give us the same influence toward the growth of fresh water lobster. The composition of biochemic food with the containing protein around 10,7%,13.34% and 13,38% has given the same effect to the lobster growth on post larva 60 level. There is strong correlation between abdomen and cephalothorax and between the total length and the lobsters weight.